Implementation of Rice Fish Farming as an Environmentally Friendly Alternative for Pest and Weed Control to Support Food Security in Talotenreng Village - Ambo Upe; Muhammad Adhan; Novita Dwi Yanti; Harmin Adijaya Putri; Sri Hardianti Rosadi (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Lingungan Hidup, 2023)
One of the main problems faced by farmers is the decline in farming productivity, resulting in farmer incomes also not decreasing. Apart from that, the problem of pests and weeds is also a polemic for farmers who always rely on artificial chemicals to control them. As long as the farming system run by partner farmers is still monoculture, the farming results obtained only come from one commodity. Farmers have not yet aimed at diversifying their farming, so the income they earn is very dependent on the success of their monoculture farming. The solution offered to partners to the decline in production followed by the degradation of agricultural land whose quality is increasingly decreasing is to refer to the concept of organic farming, where the use of fertilizer production facilities is directed at the use of agricultural waste as a substitute for inorganic fertilizer, apart from being a fertilizer, also as food for fish that is environmentally friendly. Apart from that, the solution offered is the application of an integrated agricultural system with the